Coronavirus Disease 2019 (COVID-19) Breakthrough Infection and Post-Vaccination Neutralizing Antibodies Among Healthcare Workers in a Referral Hospital in Tokyo: A Case-Control Matching Study - Yamamoto, Shohei; Maeda, Kenji; Matsuda, Kouki; Tanaka, Akihito; Horii, Kumi; Okudera, Kaori; Takeuchi, Junko S; Mizoue, Tetsuya; Konishi, Maki; Ozeki, Mitsuru; Sugiyama, Haruhito; Aoyanagi, Nobuyoshi; et al. (Clinical infectious diseases, 2022)
Abstract Background While increasing coverage of effective vaccines against coronavirus disease 2019 (COVID-19), emergent variants raise concerns about breakthrough infection. Data are limited, however, whether breakthrough infection during the epidemic of the variant is ascribed to insufficient vaccine-induced immunogenicity. Methods We describe incident COVID-19 in relation to the vaccination program among workers of a referral hospital in Tokyo. During the predominantly Delta epidemic, we followed 2415 fully vaccinated staff (BNT162b2) for breakthrough infection and selected 3 matched controls. We measured post-vaccination neutralizing antibodies against the wild-type, Alpha (B.1.1.7), and Delta (B.1.617.2) strains using live viruses and anti-spike antibodies using quantitative assays, and compared them using the generalized estimating equation model between the 2 groups. Results No COVID-19 cases occurred 1–2 months after the vaccination program during the fourth epidemic wave in Japan, dominated by the Alpha variant, while 22 cases emerged 2–4 months after the vaccination program during the fifth wave, dominated by the Delta variant. In the vaccinated cohort, all 17 cases of breakthrough infection were mild or asymptomatic and participants had returned to work early. There was no measurable difference between cases and controls in post-vaccination neutralizing antibody titers against the wild-type, Alpha, Delta, and anti-spike antibody titers, while neutralizing titers against the variants were considerably lower than those against the wild-type. Conclusions Post-vaccination neutralizing antibody titers were not decreased among patients with breakthrough infection relative to their controls under the Delta variant outbreak. The result points to the importance of infection-control measures in the post-vaccination era, irrespective of immunogenicity profile. During a large epidemic wave of the SARS-CoV-2 Delta variant in Japan, post-vaccination neutralizing antibodies against the wild-type, Alpha, and Delta variants did not materially differ between healthcare workers who experienced breakthrough infection and those who did not.